Robust RSA distributed signatures for large-scale long-lived ad hoc networks - Zanin, Giorgio; Di Pietro, Roberto; Mancini, Luigi V. (Journal of computer security, 2007)
Ad hoc environments are subject to tight security and architectural constraints, which call for distributed, adaptive, robust and efficient solutions. In this paper we propose a distributed signature protocol for large-scale long-lived ad hoc networks. The proposed protocol is based on RSA and a new ( t , t ) -secret sharing scheme. The nodes of the network are uniformly partitioned into t classes, and the nodes belonging to the same class are provided with the same share. Any t nodes, belonging to different classes, can collectively issue a signature, without any interaction. The scheme is at least as secure as any ( t , n ) -threshold scheme, i.e., an adversary can neither forge a signature nor disrupt the computation, unless it has compromised at least t nodes, belonging to different classes. Moreover, an attempt to disrupt the distributed service, by providing a fake signature share, would reveal the cheating node. Further, it is possible to easily increase the level of security, by shifting from a ( t , t ) to a ( t + k , t + k ) scheme, for a reasonable choice of parameter k, involving just a fraction of the nodes, so that the scheme is adaptive to the level of threat that the ad hoc network is subject to. Finally, the distributed signature protocol is efficient: the number of messages sent and received for generating a signature, as well as to increase the level of security, is small and both computations and memory required are small as well.